Evidence for Deep Phylogenetic Conservation of Exonic Splice-Related Constraints: Splice-Related Skews at Exonic Ends in the Brown Alga Ectocarpus Are Common and Resemble Those Seen in Humans - Wu, XianMing (Oxford University Press, 2013)
The control of RNA splicing is often modulated by exonic motifs near splice sites. Chief among these are exonic splice enhancers (ESEs). Well-described ESEs in mammals are purine rich and cause predictable skews in codon and amino acid usage toward exonic ends. Looking across species, those with relatively abundant intronic sequence are those with the more profound end of exon skews, indicative of exonization of splice site recognition. To date, the only intron-rich species that have been analyzed are mammals, precluding any conclusions about the likely ancestral condition. Here, we examine the patterns of codon and amino acid usage in the vicinity of exon–intron junctions in the brown alga Ectocarpus siliculosus, a species with abundant large introns, known SR proteins, and classical splice sites. We find that amino acids and codons preferred/avoided at both 3′ and 5′ ends in Ectocarpus, of which there are many, tend, on average, to also be preferred/avoided at the same exon ends in humans. Moreover, the preferences observed at the 5′ ends of exons are largely the same as those at the 3′ ends, a symmetry trend only previously observed in animals. We predict putative hexameric ESEs in Ectocarpus and show that these are purine rich and that there are many more of these identified as functional ESEs in humans than expected by chance. These results are consistent with deep phylogenetic conservation of SR protein binding motifs. Assuming codons preferred near boundaries are “splice optimal” codons, in Ectocarpus, unlike Drosophila, splice optimal and translationally optimal codons are not mutually exclusive. The exclusivity of translationally optimal and splice optimal codon sets is thus not universal.